Analysis of Supply Chain Policy Effects on Employment and Unemployment in the Republic of Tatarstan - Valeria Leonidovna Vorontsova; Svetlana Nikolaevna Savdur; Elena Leonidovna Fesina; Askar Nailevich Mustafin (International Journal of Supply Chain Management, 2019)
Abstract- The development of the Russian model of the labor market and its individual elements and supply chain strategy is described by a number of Russian and foreign scholars. Its main meaning is in the weak sensitivity of quantitative indicators of employment and unemployment to the dynamics of production, and over-adaptability and extreme wage flexibility. The Republic of Tatarstan has a fairly high level of employment, which conceals a significant heterogeneity of jobs. One consequence of this is the high poverty of educated people with jobs. Despite the fact that the Russian labor legislation prescribes a kind of â€œstandardâ€ of employment, involving a permanent employment contract and full-time work, market reforms significantly diversifiedtypes of employment. Formally, deviations from the prescribed standard are allowed only in special cases that are listed in the legislation. However, in a short time, various deviations from both the â€œstandardâ€ itself and the list of allowed exceptions became spread in the labor market in the Republic of Tatarstan. This led to the emergence of atypical forms of employment: unofficial, part-time, overtime, temporary. Such forms of employment facilitate a real adjustment of the supply and demand in the Tatarstan labor market. The paperconsiders the approaches to a comprehensive economic and statistical analysis of employment and unemployment in the Republic of Tatarstan in the conditions of their diversification in the new economic order.